Answer:
<em> </em><em>here </em><em>9</em><em>*</em><em>1</em><em>0</em><em>^</em><em>4</em><em> </em><em>is </em><em>a </em><em>square </em><em>number </em>
Step-by-step explanation:
<em>9</em><em>*</em><em>1</em><em>0</em><em>^</em><em>4</em><em> </em><em>=</em><em> </em><em>9</em><em>0</em><em>0</em><em>0</em><em>0</em>
<em>and </em><em>it </em><em>is </em><em>a </em><em>square </em><em>of </em><em>3</em><em>0</em><em>0</em><em> </em>
UV/TW=UX/WX this is the answer
Answer:f−1(x)=√2(x+8)2,−√2(x+8)2
Step-by-step explanation:
Interchange the variables. Solve for y. Solve for y and replace with f^-1(×). Replace the y with f^-1 (x) to show the answer.
Answer:
B. 0
Step-by-step explanation:
Given
g(t) = t² - t
f(x) = 1 + x
Required
Find g(f(3) - 2f(1))
First, we'll solve for f(3)
Given that f(x) = 1 + x
f(3) = 1 + 3
f(3) = 4
Then, we'll solve for 2f(1)
2f(1) = 2 * f(1)
2f(1) = 2 * (1 + 1)
2f(1) = 2 * 2
2f(1) = 4
Substitute the values of f(3) and 2f(1) in g(f(3) - 2f(1))
g(f(3) - 2f(1)) = g(4 - 4)
g(f(3) - 2f(1)) = g(0)
Now, we'll solve for g(0)
Given that g(t) = t² - t
g(0) = 0² - 0
g(0) = 0 - 0
g(0) = 0
Hence, g(f(3) - 2f(1)) = 0
From the list of given options, the correct answer is B. 0
All the components in the state vector need to sum to 1. You're given that component corresponding to state 1 is 0.2, and that the component for state 3 is 0.
That leaves states 2 and 4, for which you're told that the component for state 2 is four times as large. If
is the component for state
, then you have
which means
. So the state vector is
.